(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
The paper addresses the importance of the topic: The Professional improvement of agricultural teachers in pedagogical professional orientation. It recognizes methodological limitations and insufficiently treated theoretical spaces, basing itself on the dialectical materialist method as a general methodology and is supported by other scientific methods, at the theoretical, empirical, mathematical and/or statistical level. It offers a foundation with reference international and national theoretical studies, based on the approach of lifelong learning. In response to the needs confirmed during the diagnosis, links and relationships are established between the school and the locality. The involvement of municipal decision makers and local actors in the process of professional improvement and their intention to contribute to local development is highlighted.